A EXCENTRICIDADE DOS PLANETAS E A PRIMEIRA LEI DE KEPLER: ATIVIDADE DE PROVA EXPERIMENTAL - Alves Boldrini Cabral, Sabrina; Scheid Gazire, Eliane (LINKSCIENCEPLACE, 2026)
In this work, we present a clipping of the research "Developing Geometric Argumentative Thinking: Constructing Investigative Practices" presented to the Master’s program in Science and Mathematics Teaching at PUC Minas. The present research was developed in the sense of proposing teaching situations that lead the student to: observe, experiment, reflect, conjecture and refute. The activity described here, "The Eccentricity of the Planets and the First Law of Kepler", was constructed with the objective of analyzing, according to the model proposed by Balacheff (2000), the level of geometric evidence found in the arguments of the 3rd year students as well as presenting evidence that the teaching of evidence and demonstrations, based on experimentation, can lead the student to develop a higher level of geometric understanding. In this sense, we present in this work some data resulting from the application of this activity in the classroom followed by some related reflections.